PENGEMBANGAN SOFT SKILLS DAN RELEVANSINYA TERHADAP PEMBENTUKAN AKHLAK MAHASISWA: PERSPEKTIF HADIS - Munawarah Munawarah; Raudah Abshari (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2019)
A personâ€™s success is not determined solely by the knowledge and technical abilities (hard skills). But rather by the ability to manage themselves and others (soft skills) relating to factors of emotional intelligence (EQ). Because soft skills is critical given in the educational process. Inability to provide soft skills training will only result in graduates who are just good at memorizing lessons and get a little bit of skill when already in employment. Currently we are in the middle of the vortex hegomonia media, science and technology revolution. Not only is able to bring the ease and comfort of living for humans, but also invite problems and concerns. Progress in science and technology can reduce the humanitarian values or dehumanization. In the reality on the ground, moral development efforts through a variety of educational institutions and various methods continue to be developed. It shows that morality does need to be nurtured. Based on the hadith â€œBehold, I am sent by God to enhance budipekerti nobilityâ€ (HR. Ahmad). This type of research is qualitative research methods literature, namely data collection is done through the places of storage of research results. The data collection technique using the method of documentation, namely reference books that can be justified. Examination of the validity of data tend to use triangulation techniques theory. In this research using descriptive method with content analysis techniques, which draw a conclusion through the efforts of finding the characteristics of the message and be conducted objectively and systematically.